2010
DOI: 10.1016/j.jacl.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D is associated with atheroprotective high-density lipoprotein profile in postmenopausal women

Abstract: BACKGROUND Low vitamin D has been associated with low levels of high-density lipoprotein (HDL) cholesterol, a marker of coronary risk. Whether atheroprotective HDL particle composition accounts for this association and whether fat affects this association is not known. OBJECTIVE To explore the association between HDL particle composition and 25-hydroxy vitamin D (25[OH]D) in post-menopausal women. METHODS Vitamin D levels and lipoprotein composition were assessed in fasting blood samples of apparently heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 29 publications
9
27
0
Order By: Relevance
“…Reis et al [5] found that vitamin D was associated with HDL-C and adiposity in adolescents. In contrast, a recent study found that the association between vitamin D and HDL-C was independent of adiposity [20]. Consistent with this recent study, we found that the association between vitamin D and HDL-C was independent of BMI in the regression model.…”
Section: Discussionsupporting
confidence: 89%
“…Reis et al [5] found that vitamin D was associated with HDL-C and adiposity in adolescents. In contrast, a recent study found that the association between vitamin D and HDL-C was independent of adiposity [20]. Consistent with this recent study, we found that the association between vitamin D and HDL-C was independent of BMI in the regression model.…”
Section: Discussionsupporting
confidence: 89%
“…Another possible cardio-protective effect of vitamin D may be via lipid regulation, as the association between vitamin D deficiency and a less favourable lipid profile has been reported earlier (1,2,11,13,41). The positive correlation between 25(OH)D and HDL in postmenopausal women also seen in DOPS has previously been investigated and the subclass of large HDL was accounting for the difference (42). The positive correlation between 25(OH)D and HDL and inverse correlation of 25(OH)D with triglycerides are in line with the increased intima media thickness seen in subjects with carotid plaques from The Northern Manhattan Study (43).…”
Section: Discussionmentioning
confidence: 81%
“…As such, these women should receive educational sessions on healthy lifestyles, which revolve around emphasizing regular physical activity, avoiding or stopping smoking, avoiding excessive alcohol consumption, maintaining a normal body weight, and adopting a healthy diet [2,19,20]. Omega-3 fatty acids may be administered in high-risk women, as well as folic acid, vitamin K and vitamin D [19,21,22]. On another hand, glucose intolerance and diabetes should be screened, and women suffering from diabetes should receive adequate management to prevent or delay related complications.…”
Section: Discussionmentioning
confidence: 99%